Analisis Pengendalian Kualitas untuk Meminimalisir Kecacatan Produk Paving Block Menggunakan Metode Statistical Quality Control (SQC) dan Failure Mode and Effect Analysis (FMEA) - Utami, Silvia Firda; Septiana, Widya (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
CV. Maras Beton is one of the paving block manufacturers in Sumbawa that continues to face challenges in maintaining product quality. A large number of defective paving blocks go unrecorded, indicating weak quality control, which leads to an increasing number of defects and financial losses for the company. This study aims to identify and propose solutions to these product defects using the Statistical Quality Control (SQC) and Failure Mode and Effect Analysis (FMEA) methods. Based on a sample drawn from a population of 98, the SQC analysis using five tools identified four main types of defects: cracks, porous surfaces, chipped edges, and breakage, with a monthly increase in defect trends. Although the dominant defect varies each month, cracks are the most frequent, accounting for 26.8% of total defects. FMEA results show the highest RPN values stem from material factors (unmeasured sand moisture), method (manual measuring), and human factors (workers rushing). Recommended improvements include using a moisture meter, standardizing volume measurements, and scheduling product transfers more efficiently.